2020
DOI: 10.1534/g3.120.401014
|View full text |Cite
|
Sign up to set email alerts
|

Independent Whole-Genome Duplications Define the Architecture of the Genomes of the Devastating West African Cacao Black Pod PathogenPhytophthora megakaryaand Its Close RelativePhytophthora palmivora

Abstract: Phytophthora megakarya and P. palmivora are oomycete pathogens that cause black pod rot of cacao (Theobroma cacao), the most economically important disease on cacao globally. While P. palmivora is a cosmopolitan pathogen, P. megakarya, which is more aggressive on cacao than P. palmivora, has been reported only in West and Central Africa where … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 117 publications
0
21
0
Order By: Relevance
“…Despite this, in a study conducted in six cocoa-growing regions in West Africa, where sixteen Phytophthora isolates were analysed, it was found that these isolates were more virulent and they reproduced faster than P. megakarya [ 20 ]. Recently, Morales-Cruz et al [ 21 ] demonstrated that P. megakarya genome is extensive (222 Mbp) and nearly twice the size of P. palmivora (135 Mbp) and most known Phytophthora species (∼100 Mbp on average). Ali et al [ 16 ] found that P. megakarya shows a different virulence-related gene complement, similar in size and potentially of greater diversity than P. palmivora .…”
Section: Preharvestmentioning
confidence: 99%
“…Despite this, in a study conducted in six cocoa-growing regions in West Africa, where sixteen Phytophthora isolates were analysed, it was found that these isolates were more virulent and they reproduced faster than P. megakarya [ 20 ]. Recently, Morales-Cruz et al [ 21 ] demonstrated that P. megakarya genome is extensive (222 Mbp) and nearly twice the size of P. palmivora (135 Mbp) and most known Phytophthora species (∼100 Mbp on average). Ali et al [ 16 ] found that P. megakarya shows a different virulence-related gene complement, similar in size and potentially of greater diversity than P. palmivora .…”
Section: Preharvestmentioning
confidence: 99%
“…Hence, the identification and characterisation of core effectors, which are deployed by P. palmivora in Colombia to surpass the immunity of cocoa plant varieties, could be extremely useful in deploying effector-aided resistant breeding that is less time consuming and more durable than conventional breeding strategies (Evangelisti et al, 2017). These effector studies could be aided by a recent study that redefined the genomic structure of P. palmivora, allowing for the identification of several new effectors from this pathogen (Morales-Cruz et al, 2020).…”
Section: Phytophthora Palmivoramentioning
confidence: 99%
“…Genome, transcriptome and secretome studies combined with RNA-sequencing and RT-PCR identified RXLR effectors and crinklers in Ppal and P. megakarya, which were differentially expressed in mycelia, zoospores, and in planta (infected pod husks) [ 106 ]. Furthermore, recent work by Morales–Cruz et al [ 136 ] predicted that Ppal had 717 RxLR effectors compared to P. megakarya, which had 1,382 effectors due to genome duplication and expansion in the latter. In addition, 251 “putative effectors” in Ppal had shared homology and often bordered RxLRs [ 136 ].…”
Section: Overcoming Plant Host Immunity By Ppal and Other Oomycetementioning
confidence: 99%
“…Furthermore, recent work by Morales–Cruz et al [ 136 ] predicted that Ppal had 717 RxLR effectors compared to P. megakarya, which had 1,382 effectors due to genome duplication and expansion in the latter. In addition, 251 “putative effectors” in Ppal had shared homology and often bordered RxLRs [ 136 ]. More work would be needed to understand the functions of these effectors in Ppal and how they aid in infection and in manipulating cocoa’s immunity to cause disease.…”
Section: Overcoming Plant Host Immunity By Ppal and Other Oomycetementioning
confidence: 99%